PENGADAAN BARANG KEBUTUHAN KAMAR DEPARTEMEN HOUSEKEEPING DI HOTEL HW PADANG - Satria, Imam Ali; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2016)
This research is motivated by the procurement needs of rooms are less well seen from the specifications for goods less detail, the lack of transparency in the procurement of goods made by the purchasing, then the lack of effective procurement of goods made by the purchasing. This study aimed to describe the principle of the supply of goods, namely: effective, efficient, and openness in HW Padang. This research is a descriptive study with qualitative data. Data was collected using interviews, observation and documentation. The sampling technique used was purposive sampling consisting of Housekeeping department manager as much as 2 people and implementing the procurement needs of rooms 2 people. Based on the results of a study of the department head, user housekeeping, purchasing and cost control found some aspects related to the procurement needs of rooms are: Efficient procurement needs of rooms departmental housekeeping were still not optimally in terms of working methods, there are some tasks where yet in accordance with existing rules, especially in the procurement of goods. Then with regard to effective procurement department needs housekeeping room which is in conformity with existing rules. Then openness in the procurement department needs housekeeping room which is still not good, especially in the Bid made by purchasing the supplier.Key words : Procurement , efficient , effective , openness1Prodi D4